Antibacterial Activity and Bioautography of the Chloroform Fraction of Morel Berry (Physalis angulata L.) Root Against Staphylococcus epidermidis and Pseudomonas aeruginosa - Pratika Viogenta; Laila Susanti; Latifah Megasari (Pandawa Institute, 2023)
The urgency of finding novel sources of active compounds to overcome infectious diseases is encouraged. Morel berry (Physalis angulata L.) is a traditional herbal plant that can be used as an antimicrobial because of its unique chemical content. This study aims to find compounds that have antibacterial activity from the chloroform fraction of morel berry roots. This study used the Kirby-Bauer method with concentrations of 20%, 40%, 60%, 80%, and 100% against Staphylococcus epidermidis and Pseudomonas aeruginosa bacteria. Determination of antibacterial compounds and their functional groups was performed using thin-layer chromatography (TLC) technique and reagent spray test, TLC-Bioautography and Fourier transforms infrared (FTIR) studies. The chloroform fraction of morel berry showed a zone of inhibition with the highest diameter of 11.50 and 12.00 mm against S. epidermidis and P. aeruginosa, respectively. Phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, and saponins in the chloroform fraction. The relative retention stain of 0.54 on the TLC plate inhibited the growth of the two tested bacteria and indicated the presence of functional groups O-H phenol, C-H aliphatic, C=O ester, C=C aromatic, C-OH alcohol, and C-H aromatic. This study found that tannins in the roots of morel berries could be used as a natural antibacterial agent to treat S. epidermidis and P. aeruginosa.